Моделювання та оцінка економічних наслідків зміни політики субсидіювання на ринку природного газу України - Чепелєв, М.Г. (Економіка промисловості, 2014)
На базі статичної обчислювальної моделі загальної рівноваги України, з диференційованими за рівнем доходів домогосподарствами, досліджено соціально-економічні наслідки зменшення обсягів субсидіювання побутових споживачів природного газу, пари та гарячої води. Оцінено ефективність різних форм компенсаційних заходів, які дозволяють здійснити приведення тарифів на енергоресурси до економічно обґрунтованого рівня у соціально прийнятний спосіб. На базе статической вычислительной модели общего равновесия Украины, с дифференцированными по уровню доходов домохозяйствами, исследованы социально-экономические последствия сокращения объемов субсидирования бытовых потребителей природного газа, пара и горячей воды. Оценена эффективность различных форм компенсационных мероприятий, которые позволяют осуществить приведение тарифов на энергоресурсы к экономически обоснованному уровню социально приемлемым способом. In Ukraine natural gas consumption subsidies are widely used as an economic policy measure. According to the IEA estimates in 2012 they amounted to 4,5% of GDP or 16% of Central government budget. And while in general such policy options should address crucial socio-economic issues, in practice they fail to do that. Natural gas subsidies in Ukraine not only create a severe pressure on the public finances but also preferentially allocate money to the high-income households. In particular, households of the richest (X-th decile) receive three times more heat subsidies than the poorest 10% (I-st decile) of public users. In addition this policy distorts market pricing, leads to the inefficient resources allocation, negative environmental effects and energy security decrease.Considering this issue Ukrainian government has initiated a tariff reform in the energy sector. Within the fist stage (2014), residential heat tariffs would be increased by 40%, while average natural gas price for households would rise by 56%. Although this step is of great significance, it generates a lot of practical questions in terms of reform implementation. They include, among others, valuation of the proposed compensation measures efficiency and their influence on the payment discipline, effective distribution of the additionally received funds, and search for the compensation costs recovery sources, etc.To explore these issues the paper adopts a static computable general equilibrium model with heterogeneous households and extended energy sector. Within this modelling tool, apart from government, final consumers are divided into ten groups according to the income level, producers are represented via 40 economic activities, and separate treatment is given to the investors, retirement and social security funds.As modeling results show, while in the long term subsidies elimination leads to the moderate positive macroeconomic effects, in the short term households face sensible real income decrease (0,8%- 2,2%), which is additionally amplified against the background of existing economic and political predicament.Progressive taxation proved to be the most effective among the compensation costs recovery options studied. Firstly, it does not adversely influence the government budget. Secondly, it induces positive macroeconomic effects. Finally, it serves as a damper for tariff reform regressive consequences and income inequality.In the context of mid- and long-term economic growth perspectives and Ukrainian energy security, at least moderated tariff increase for natural gas producers should be a foreground issue, especially considering the opportunities of gas production volumes increase.